Coexistence of bipolar non-volatile and threshold volatile resistive switching in MoS2 nanosheets treated by soft nitrogen plasma. (25th November 2019) - Ke, Yizhen; Zhang, Zidong; Guo, Junxiong; Mao, Linna; Cheng, Tiedong; Zhou, Haiping; Lin, Yuan; Gong, Tianxun; Huang, Wen; Zhang, Xiaosheng
Abstract: Coexistence of non-volatile and volatile resistive switching on the same device are of interest in memory devices for weight storage applications. In this work, stacked MoS2 nanosheet thin film was modified using soft nitrogen plasma treatment (NPT). Compared to pristine MoS2 -based counterparts, the fabricated Ag/NPT-MoS2 /indium tin oxide (ITO) structure exhibited both an enhanced ratio of 10 4 and lowered threshold voltage of 0.1 V. The distinction might be attributed to the introduced carbonitride between Ag and MoS2, where the conductive filaments and interface barrier altogether affect the switching. The observation suggested a possibility of programming on a single two-terminal device.